The Potency of Moringa oleifera Lam. as Protective Agent in Cardiac Damage and Vascular Dysfunction - Alia, Fenty; Putri, Mirasari; Anggraeni, Neni; Syamsunarno, Mas Rizky A. A (Frontiers in Pharmacology, 2022)
Cardiac damage and vascular dysfunction due to underlying diseases, such as hypertension and cardiac thrombosis, or side effects from certain drugs may lead to critical illness conditions and even death. The phytochemical compounds in natural products are being prospected to protect the heart and vascular system from further damage. Moringa genus is a subtropical tree native to Asia and Africa, which includes 13 species; Moringa oleifera (MO) is the most cultivated for its beneficial uses. MO is also known as the “miracle tree” because it has been used traditionally as a food source and medicine to treat various diseases such as anemia, diabetes, and infectious or cardiovascular diseases. The phytochemical compounds identified in MO with functional activities associated with cardiovascular diseases are N, α-L-rhamnopyranosyl vincosamide, isoquercetin, quercetin, quercetrin, and isothiocyanate. This study aims to investigate the potency of the phytochemical compounds in MO as a protective agent to cardiac damage and vascular dysfunction in the cardiovascular disease model. This is a scoping review by studying publications from the reputed database that assessed the functional activities of MO, which contribute to the improvement of cardiac and vascular dysfunctions. Studies show that the phytochemical compounds, for example, N, α-L-rhamnopyranosyl vincosamide, and quercetin, have the molecular function of antioxidant, anti-inflammation, and anti-apoptosis. These lead to improving cardiac contractility and protecting cardiac structural integrity from damage. These compounds also act as natural vasorelaxant and endothelium protective agent. Most of the studies were conducted in animal; therefore, further studies are necessary to be applied in a clinical setting.